PENGARUH PERSEPSI KONSUMEN PADA IKLAN BERSERI TERHADAP SIKAP DAN NIAT BELI KONSUMEN (Studi eksperimen pada produk kosmetika Ponds) - , ANA BELLA PARINA, Dr. Ir. Suci Paramitasari Syahlani, M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Marketing research is important to assist the whole marketing system in managerial decision making through relevant, accurate, and on-time information. One of the marketing aspects most frequently investigated concerns with marketing communication and consumer behavior. Marketing communication is conducted by producers through numerous methods, including advertisements, sales promotions, experiences, public relation and notification, direct selling, and ual media has been considered as one of the most effective promotion mix instruments used in deliverin create consumer perception and attitude ement with e effects of consumer ercept personal selling. Among the promotion efforts, television advertisement using audio vis g messages to for consumers purchase intention and even purchasing decision. To attract consumer interest to watch advertisement presented, a company should make creative advertisement. One of them is conducted through the use of serial-dramabased advertisement as implemented in the Pondsâ cosmetics product advertisement. This research aimed to identify whether consumer perception on the serial advertisements of Pondsâ cosmetic products provided significant influences on consumer attitude and purchase intention, and to compare consumer perception on the consumer attitude towards serial advertising and consumer perception on the consumer attitude toward non serial advertising. In this research, the effects of consumer perception on the consumer attitude and consumer purchase intention towards Pondsâ cosmetics products were measured. This was an experimental research with participants divided into 2 groups, namely, participant group treated with serial advertisement, and participant group treated with non serial-advertisement. Research instruments exploited involved advertisement video samples of Pondsâ cosmetics and research questionnaires. Total samples were 60 persons in each group of serial advertisement and non serial-advertisement. Data obtained were analyzed using simple regression and significance test through the use of SPSS 17 for Windows. Based on the regression analysis, it was showed that the significant effects of consumer perception on the consumer attitude toward serial advertis t-test 8,205, the significant effects of consumer perception on serial advertisement towards consumer purchasing intention with t-test 8,797, and the significant effects of consumer attitude on the serial advertisement toward consumer purchasing intention wiht t-test 6,274. After comparison between the effects of consumer perception on consumer attitude towards serial advertisement, and the effects of the effects of consumer perception on the consumer attitude on nonserial advertisement using t-test it was indicated that th p ion on the consumer attitude toward serial advertisement was higher than the consumer perception towards the consumer attitude on non-serial advertisement.